A mitochondria-targeted supramolecular nanoplatform for peroxynitrite-potentiated oxidative therapy of orthotopic hepatoma. (November 2022) - Dai, Wenbin; Deng, Yongyan; Chen, Xiaohui; Huang, Yue; Hu, Haitao; Jin, Qiao; Tang, Zhe; Ji, Jian
Abstract: Oxidative therapy, which generates reactive oxygen species (ROS) via intracellular enzymatic reactions to achieve tumor ablation, is considered as an emerging approach to cancer treatment. Herein, nitric oxide (NO)-combined oxidative therapy is reported by integrating glutathione (GSH)-sensitive NO donor and pH-sensitive cinnamaldehyde (CA) prodrug into a mitochondria-targeted drug nanocarrier, which is prepared by the host-guest interaction between α-cyclodextrin (α-CD) and polyethylene glycol (PEG). After internalized by cancer cells, CA can be released in acidic endo/lysosome and finally induce ROS generation in mitochondria for oxidative therapy. At the same time, NO can be targeted delivered to mitochondria by a mitochondria-targeting strategy and then realize selective release of NO in mitochondria. NO can deplete intracellular predominant antioxidant GSH, which will enhance oxidative therapy of CA. Furthermore, peroxynitrite (ONOO − ) with strong peroxidation and nitration capability can be produced in mitochondria by the reaction between NO and ROS for reactive nitrogen species (RNS)-mediated oxidative therapy. The generation of ONOO − in mitochondria is very effective in facilitating mitochondrial membrane permeabilization, which can cause mitochondrial dysfunction and finally induce mitochondrial apoptosis. The antitumor ability of mitochondria-targeted ONOO − -potentiated oxidative therapy is fully investigated on subcutaneous and orthotopic hepatoma model on nude mice. This innovative strategy for the selective generation of ONOO − in mitochondria may serve as an afflatus for future applications in cancer treatment.